STUDY OF BACTERIAL INFECTION IN UTI AND THEIR DETERMINATION OF SUSCEPTIBILITY TO ANTIBIOTICS IN POST RENAL TRANSPLANTS - J. KALAIVANI,; R. SELVI,; SHANTHA PREMA RAJ, (International Journal of Pharma and Bio Sciences, 2016)
Bacterial infections are the most common pathogenic infections, during the first month of post kidney transplantation. In this study, about 164 kidney transplanted patients were assessed for the presence of the pathogenic bacteria such as Escherichia coli, Klebsiella spp. etc. Urine samples collected from the patients were cultured for the isolation of bacteria and were identified using regular biochemical tests and antibiotic resistances assays. The incidence of infection was positive for 96 (58.54%) out of 164 patients. E. coli was mostly isolated bacteria with a frequency rate of 32.5%, followed by Klebsiella spp. (20%), Pseudomonas spp. (11.3%), Proteus spp. (8.4%), Acinetobacter spp. (7.5%), Citrobacter spp. (4.3%) and Streptococcus aureus (12.8%). All the Gram-negative bacteria were found to be sensitive to amikacin (92.4-100%) and other isolates showed sensitive to Cefotaxime, Imepenem and Gentamicin. Thus, the present study aims to implement a new prophylaxis regimen for the treatment of post-operative infection.